Teaching to Be Radical: The Women Activist Educators of Highlander - Colleen McDermott (Adult Education Research Conference, 2007)
The purpose of this study was to examine the ways in which gender has impacted the work and teaching of the women educators at Highlander. Maher and Tetreault’s (2001) themes of a feminist classroom, mastery, authority, voice and positionality, provided the theoretical framework for data analysis.